Utilization of ferulic acid in Aspergillus niger requires the transcription factor FarA and a newly identified Far-like protein (FarD) that lacks the canonical Zn(II)2Cys6 domain - Arentshorst, Mark; Reijngoud, Jos; van Tol, Daan J. C.; Reid, Ian D.; Arendsen, Yvonne; Pel, Herman J.; van Peij, Noël N. M. E.; Visser, Jaap; Punt, Peter J.; Tsang, Adrian; Ram, Arthur F. J. (Frontiers in Fungal Biology, 2022)
The feruloyl esterase B gene (faeB) is specifically induced by hydroxycinnamic acids (e.g. ferulic acid, caffeic acid and coumaric acid) but the transcriptional regulation network involved in faeB induction and ferulic acid metabolism has only been partially addressed. To identify transcription factors involved in ferulic acid metabolism we constructed and screened a transcription factor knockout library of 239 Aspergillus niger strains for mutants unable to utilize ferulic acid as a carbon source. The ΔfarA transcription factor mutant, already known to be involved in fatty acid metabolism, could not utilize ferulic acid and other hydroxycinnamic acids. In addition to screening the transcription factor mutant collection, a forward genetic screen was performed to isolate mutants unable to express faeB. For this screen a PfaeB-amdS and PfaeB-lux613 dual reporter strain was engineered. The rationale of the screen is that in this reporter strain ferulic acid induces amdS (acetamidase) expression via the faeB promoter resulting in lethality on fluoro-acetamide. Conidia of this reporter strain were UV-mutagenized and plated on fluoro-acetamide medium in the presence of ferulic acid. Mutants unable to induce faeB are expected to be fluoro-acetamide resistant and can be positively selected for. Using this screen, six fluoro-acetamide resistant mutants were obtained and phenotypically characterized. Three mutants had a phenotype identical to the farA mutant and sequencing the farA gene in these mutants indeed showed mutations in FarA which resulted in inability to growth on ferulic acid as well as on short and long chain fatty acids. The growth phenotype of the other three mutants was similar to the farA mutants in terms of the inability to grow on ferulic acid, but these mutants grew normally on short and long chain fatty acids. The genomes of these three mutants were sequenced and allelic mutations in one particular gene (NRRL3_09145) were found. The protein encoded by NRRL3_09145 shows similarity to the FarA and FarB transcription factors. However, whereas FarA and FarB contain both the Zn(II)2Cys6 domain and a fungal-specific transcription factor domain, the protein encoded by NRRL3_09145 (FarD) lacks the canonical Zn(II)2Cys6 domain and possesses only the fungal specific transcription factor domain.